(untitled) (Costos y Gestión, 2020)
This paper purpose is to design a control board for an efficient management of the intellectual capital of the Economics Sciences Faculty, in Rio Cuartoʼs National University. For this, a descriptive study based on a model designed for the identification and valuation of the intellectual capital in the university environment was used as starting point. The study was structured in components, variables, indicators, measurement guidelines and measurement tools. Traffic lights were used for the construction of the board because of their «visual condition», meaning that, through them, it is possible to visualize the current general situation of the indicators with only one look. The traffic light was made with Microsoft Excel. The results are the analysis and control, periodically, of the indicators that present weaknesses with the possibility of being boosted through their management, aiming more efficiency and future benefits, as well as those indicators producers of value for the institution, in a way to develop competitive advantages to achieve the differentiation of the Economics Sciences Faculty of the Rio Cuartoʼs National University.